Molecular basis of the glycosomal targeting of PEX11 and its mislocalization to mitochondrion in trypanosomes - Krishna, Chethan K.; Schmidt, Nadine; Tippler, Bettina G.; Schliebs, Wolfgang; Jung, Martin; Winklhofer, Konstanze F.; Erdmann, Ralf; Kalel, Vishal C. (Frontiers in Cell and Developmental Biology, 2023)
PEX19 binding sites are essential parts of the targeting signals of peroxisomal membrane proteins (mPTS). In this study, we characterized PEX19 binding sites of PEX11, the most abundant peroxisomal and glycosomal membrane protein from Trypanosoma brucei and Saccharomyces cerevisiae. TbPEX11 contains two PEX19 binding sites, one close to the N-terminus (BS1) and a second in proximity to the first transmembrane domain (BS2). The N-terminal BS1 is highly conserved across different organisms and is required for maintenance of the steady-state concentration and efficient targeting to peroxisomes and glycosomes in both baker's yeast and T. brucei. The second PEX19 binding site in TbPEX11 is essential for its glycosomal localization. Deletion or mutations of the PEX19 binding sites in TbPEX11 or ScPEX11 results in mislocalization of the proteins to mitochondria. Bioinformatic analysis indicates that the N-terminal region of TbPEX11 contains an amphiphilic helix and several putative TOM20 recognition motifs. We show that the extreme N-terminal region of TbPEX11 contains a cryptic Nterminal signal that directs PEX11 to mitochondrion if its glycosomal transport is blocked.